Iota-carrageenan as sustainable bio-adsorbent for the removal of europium ions from aqueous solutions. (August 2022) - Levy-Ontman, Oshrat; Yanay, Chanan; Paz-Tal, Ofra; Wolfson, Adi
Abstract: The use of algae cell-wall polysaccharides to adsorb heavy metals from wastewaters has motivated a lot of work in the field. Though these molecules possess properties that seem to render them applicable as metal adsorbents, their full potential has yet to be realized. To that end, we developed a simple and straightforward technique to remove europium ions from aqueous solutions by using three representative polysaccharides: guar gum, xanthan gum and iota-carrageenan. The sorption yield increased in correlation with the acidity of the functional groups on these representative polysaccharides. A comparison of the Fourier-transform infrared spectra of the guar gum/xanthan gum/iota-carrageenan hydrogels formed following the europium adsorption to that of pristine polysaccharides indicated that they comprised different transmission bands, suggesting that europium ion adsorption occurs via interactions with the functional groups on the polysaccharides. Furthermore, scanning electron microscopy of iota-carrageenan hydrogel confirming that the europium was adsorbed to the iota-carrageenan and the europium:sulfur ratio of about 2.8:1 suggest that europium was linked to ~3 ester sulfate groups by inter/intramolecular forces via the oxygen atom. In addition, X-ray photoelectron analysis showed that the ratio of the peaks Eu +2 /Eu +3 in iota-carrageenan hydrogel were markedly intensified relative to its respective ratio in Eu(NO3 )3 ⋅6 H2 O. Graphical Abstract: ga1